On the current status of Phakopsora pachyrhizi genome sequencing - Loehrer, Marco; Vogel, Alexander; Huettel, Bruno; Reinhardt, Richard; Benes, Vladimir; Duplessis, Sébastien; Usadel, Björn; Schaffrath, Ulrich (Frontiers in Plant Science, 2014)
Recent advances in the field of sequencing technologies and bioinformatics allow a more rapid access to genomes of non-model organisms at sinking costs. Accordingly, draft genomes of several economically important cereal rust fungi have been released in the last three years. Aside from the very recent flax rust and poplar rust draft assemblies there are no genomic data available for other dicot-infecting rust fungi. In this article we outline rust fungus sequencing efforts and comment on the current status of Phakopsora pachyrhizi (Asian soybean rust) genome sequencing.